Pengaruh Penggunaan Celebrity Endorser, Media Iklan Televisi Dan Pesan Iklan Televisi Shampo Sunsilk Terhadap Proses Keputusan Pembelian Konsumen Di Kota Pontianak - admin, Ade Anita Siregar B11109068 (Jurnal Manajemen Update, 2016)
This study aims to determine the effect of celebrity endorser, media television advertising and television advertising messages to the process of purchasing decisions by consumers Sunsilk shampoo in Pontianak. This study is a survey research, the entire population is a consumer product Sunsilk shampoo in Pontianak. The total sample of 100 respondents. The sampling technique in the form of accidental sampling. The criteria for the sample that is at least 17 years, acts as a purchasing decision makers, acting as Sunsilk shampoo users ever see the commercials on television Sunsilk shampoo. The findings of this study indicate that the celebrity endorser significantly influence purchasing decisions process Sunsilk shampoo in Pontianak, television advertising media significantly influence purchasing decisions process Sunsilk shampoo in Pontianak, and television advertising messages have a significant effect on purchasing decisions process Sunsilk shampoo in Pontianak. Keywords. Celebrity Endorser, Media Television Advertising, Television Advertising Message and Purchase Decision Process Â